131k views
2 votes
(X^3+1)dividend (x-1)

User Yoely
by
5.3k points

1 Answer

3 votes


x^3=x\cdot x^2 and
x^2(x-1)=x^3-x^2. So we have a remainder of


(x^3+1)-(x^3-x^2)=x^2+1


x^2=x\cdot x and
x(x-1)=x^2-x. Subtracting this from the previous remainder gives a new remainder


(x^2+1)-(x^2-x)=x+1


x=x\cdot1 and
1(x-1)=x-1. Subtracting this from the previous remainder gives a new one of


(x+1)-(x-1)=2

and we're done since 2 does not divide
x. So we have


(x^3+1)/(x-1)=x^2+x+1+\frac2{x-1}

User Chindit
by
5.8k points